Pengembangan Aplikasi Point of Sale (PoS) untuk Restoran Menggunakan JSON Server, Node JS dan Axios - Septitina Gulo, Fifiyani; Noprisson, Handrie (JSAI (Journal Scientific and Applied Informatics), 2024)
The "SSAMPAK Cashier Application" aims to present a report on the development of a web application created for the SSAMPAK Restaurant. The research methods used include field studies and observations by conducting interviews and observing the existing cashier system at the restaurant. The analysis results indicated that the manual cashier system used at SSAMPAK Restaurant is inefficient, leading to the proposal of a web-based cashier application. After discussing this proposal with the restaurant owner and the SSAMPAK IT team, the proposal was approved, and the IT team provided a database using a fake API JSON server. The purpose of developing this application is to improve the efficiency of the cashier system in the restaurant. This application has quite complete features such as grouping by category, adding menus to price, updating and deleting menu data as well as features to perform automatic calculations.